Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1502
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Simulated Driving Performance: A Pilot Study

Abstract: Summary: Twenty-seven volunteers completed three simulated driving tests to determine test-retest reliability of performance on a low-cost, fixed-base computerized driving simulator. One retest was completed a few hours after the initial drive, and the final retest was completed 7 days following the initial test drive. Driving performance was compared using measures of vehicle control, speed, and reaction time to critical events. A measure of participants' ability to inhibit a pre-potent response was also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Individuals were excluded from the study if they indicated a psychiatric disorder, head trauma, CNS injury, or current use of recreational/psychoactive drugs. Eligible participants performed a 15min familiarization drive on the simulator prior to experimental trials to reduce practice effects (Irwin, Shum, & Desbrow, 2013). Because simulator sickness can occur with simulated driving (Brooks, Goodenough, Crisler, Klein, & Alley, 2010), participants were instructed to immediately cease driving if they experienced any symptoms.…”
Section: Preliminary Screeningmentioning
confidence: 99%
“…Individuals were excluded from the study if they indicated a psychiatric disorder, head trauma, CNS injury, or current use of recreational/psychoactive drugs. Eligible participants performed a 15min familiarization drive on the simulator prior to experimental trials to reduce practice effects (Irwin, Shum, & Desbrow, 2013). Because simulator sickness can occur with simulated driving (Brooks, Goodenough, Crisler, Klein, & Alley, 2010), participants were instructed to immediately cease driving if they experienced any symptoms.…”
Section: Preliminary Screeningmentioning
confidence: 99%